Implementation of Supply Chain and Logistics for Natural Disaster Management in Indonesia: A Smart Governance Perspective - Rustian; Sumartono; Hermawan; Wardhono, Hendro (International Journal of Criminology and Sociology, 2021)
This research is at the ontological level and sociological level of the implementation of supply chain and logistics equipment for disaster management that are very significant in reducing risk of natural disaster in Indonesia. The problem is very interesting to be analyzed by conducting a descriptive qualitative research. The research used the theory of public policy, smart governance, and supply chain management and logistics. The data were collected using in-depth interview to several key informants, direct observation, and related documentation. The data were analyzed using interactive models, which were data reduction, data display, and data verification, supported by triangulation to obtain validity and reliability. The results were based on ontology, epistemology, and sociology using smart governance perspective by empowering supply chain and logistic to improve disaster management in Indonesia. Vision and mission of public policies related to natural disaster are needed to complete the facilities of prevention, equipment management and logistics supervision, providing information to stakeholders regarding regulations and sanctions in natural disaster that were carried out deliberately and balanced provision of disaster management. Therefore, it will produce a revised and detailed relevant regulation for state agencies as public officials in making regulations on natural disaster and disaster management in Indonesia. The researchers suggest that state institutions must conduct and cover smart governance in making regulations on disaster management.